A SLC39A8 variant causes manganese deficiency, and glycosylation and mitochondrial disorders. Issue 2 (19th December 2016) - Riley, Lisa G.; Cowley, Mark J.; Gayevskiy, Velimir; Roscioli, Tony; Thorburn, David R.; Prelog, Kristina; Bahlo, Melanie; Sue, Carolyn M.; Balasubramaniam, Shanti; Christodoulou, John
Summary: SLC39A8 variants have recently been reported to cause a type II congenital disorder of glycosylation (CDG) in patients with intellectual disability and cerebellar atrophy. Here we report a novel SLC39A8 variant in siblings with features of Leigh‐like mitochondrial disease. Two sisters born to consanguineous Lebanese parents had profound developmental delay, dystonia, seizures and failure to thrive. Brain MRI of both siblings identified bilateral basal ganglia hyperintensities on T2‐weighted imaging and cerebral atrophy. CSF lactate was elevated in patient 1 and normal in patient 2. Respiratory chain enzymology was only performed on patient 1 and revealed complex IV and II + III activity was low in liver, with elevated complex I activity. Complex IV activity was borderline low in patient 1 muscle and pyruvate dehydrogenase activity was reduced. Whole genome sequencing identified a homozygous Chr4(GRCh37):g.103236869C>G; c.338G>C; p.(Cys113Ser) variant in SLC39A8, located in one of eight regions identified by homozygosity mapping. SLC39A8 encodes a manganese and zinc transporter which localises to the cell and mitochondrial membranes. Patient 2 blood and urine manganese levels were undetectably low. Transferrin electrophoresis of patient 2 serum revealed a type II CDG defect. Oral supplementation with galactose and uridine led to improvement of the transferrin isoform pattern within 14 days of treatment initiation. Oral manganese has only recently been added to the treatment. These results suggest SLC39A8 deficiency can cause both a type II CDG and Leigh‐like syndrome, possibly via reduced activity of the manganese‐dependent enzymes β‐galactosyltransferase and mitochondrial manganese superoxide dismutase.